2017
DOI: 10.15226/2637-6121/1/1/00102
|View full text |Cite
|
Sign up to set email alerts
|

A Cross Sectional Study Highlighting the Sensitivity Patterns and Incidence of Extended Spectrum Beta Lactamase Producing Klebsiella oxytoca in Patients with Urinary Tract Infection

Abstract: Background and objective: Urinary tract infections (utis) due to multi-drug resistant Klebsiella oxytoca are increasing worldwide and have become a major public health problem.The aim of this study was to determine the current and local antimicrobial susceptibility pattern and frequency of ESBL positive strain of urinary K.oxytoca isolates. Material and methods: This is cross sectional observational and multicenter study with the use of non-probability sampling technique. Duration of the study was February 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
0
1
Order By: Relevance
“…This agrees with Razzaque et al 's study which found Imipenem (94.7%) and Amikacin (92.3%) as the most effective antibiotics for K. oxytoca urinary isolates. They also found sensitivity to Nitrofurantoin (84.6%) and Gentamicin (65.5%), which are different to our results 53 .…”
Section: Percent Of Sensiɵvitycontrasting
confidence: 99%
“…This agrees with Razzaque et al 's study which found Imipenem (94.7%) and Amikacin (92.3%) as the most effective antibiotics for K. oxytoca urinary isolates. They also found sensitivity to Nitrofurantoin (84.6%) and Gentamicin (65.5%), which are different to our results 53 .…”
Section: Percent Of Sensiɵvitycontrasting
confidence: 99%